2012
DOI: 10.1099/ijs.0.031054-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and emended description of Lactobacillus kunkeei as a fructophilic lactic acid bacterium

Abstract: Lactobacillus kunkeei is an inhabitant of fructose-rich niches and is a potential member of the fructophilic lactic acid bacteria. In the present study, the phylogenetic and biochemical characteristics of the type strain and eight isolates of L. kunkeei, originating from wine, flowers and honey, were studied. The nine isolates, including the type strain, formed a well-defined phylogenetic subcluster based on the analysis of 16S rRNA gene sequences. The subcluster was not closely related to other subclusters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 14 publications
10
82
1
1
Order By: Relevance
“…These M. smithiiassociated OTUs were found in both fungus-garden and worker samples (see Table S2 in the supplemental material). As already reported in McFrederick et al (16), halictids associated mainly with Lactobacillus OTUs that were related to flower-inhabiting, fructophilic lactobacilli (52) or to a clade that includes flower-inhabiting and fructophilic lactobacilli (53) and lactobacilli used in sourdough fermentation (54). Some of the halictidassociated OTUs formed monophyletic clades, but these clades did not exhibit the same level of divergence as the Firm3 and Firm4 clades (Fig.…”
Section: Resultssupporting
confidence: 62%
“…These M. smithiiassociated OTUs were found in both fungus-garden and worker samples (see Table S2 in the supplemental material). As already reported in McFrederick et al (16), halictids associated mainly with Lactobacillus OTUs that were related to flower-inhabiting, fructophilic lactobacilli (52) or to a clade that includes flower-inhabiting and fructophilic lactobacilli (53) and lactobacilli used in sourdough fermentation (54). Some of the halictidassociated OTUs formed monophyletic clades, but these clades did not exhibit the same level of divergence as the Firm3 and Firm4 clades (Fig.…”
Section: Resultssupporting
confidence: 62%
“…kunkeei has been classified as an obligate fructophilic bacteria preferring fructose as sugar source and being able to grow well on glucose only in the presence of fructose and external electron acceptors [48,49,50]. Later, it was found that L .…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic cutoffs that are commonly used in high-throughput studies to group taxa often do not align with phenotypic differences based on standard biochemical profiles or microscopy (47,48). For example, Endo et al (49) find that L. kunkeei bacteria, which are widespread in the pollination environment, in the honey bee gut, and the honey bee colony (10)(11)(12), can have nearly identical 16S rRNA gene sequences yet very different biochemical profiles. This phenotypic diversity could have great implications for the study of bacterium-bee interactions and also the use of bacteria for improving honey bee health.…”
Section: Discussionmentioning
confidence: 99%